Herpes Zoster Duplex Bilateralis in an Immunocompetent Adolescent Girl at Koshi Zonal Hospital, Morang - Baskota, Rabindra; Ghimire, A; Ghimire, S; Kathet, R (Birat Journal of Health Sciences, 2017)
Herpes Zoster (HZ) is a segmental eruption of grouped vesicles that are confined to a dermatome. There is dermatomal distribution of skin rash, which is unilateral. When two non contagious dermatomes are involved, if affected bilaterally, it is called HZ duplex bilateralis; if unilaterally, unilateralis. HZ duplex bilateralis is extremely rare in immunocompetent children. This report describes a 12-year old girl with bilateral HZ. She had no features of immunosupression. She was treated with oral acyclovir for one week. No complications, including post herpetic neuralgia, were observed during the follow up period of three months. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 234-236